2020
DOI: 10.1210/clinem/dgaa218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Description of 16 Families With Heterozygous IHH Variants

Abstract: Context Heterozygous variants in the Indian hedgehog gene (IHH) have been reported to cause brachydactyly type A1 and mild hand and feet skeletal anomalies with short stature. Genetic screening in individuals with short stature and mild skeletal anomalies has been increasing over recent years, allowing us to broaden the clinical spectrum of skeletal dysplasias. Objective The objective of this article is to describe the genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…To objectively characterize brachydactyly in this family, we performed a metacarpophalangeal pattern profile (MCPP) for the three patients, which did demonstrate not only brachymesophalangy and brachymatacarpia but brachytelephalaby, which recapitulated what Sentchordi-Montané et al reported and resembled those seen in ACFD (Figure S1). 6 In agreement with the previous report by Sentchordi-Montané et al, 5 we found that IHH heterozygous variants caused broader clinical and radiological manifestations than previously thought. The clinical manifestations of IHH heterozygous variants are variable even within the same family.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…To objectively characterize brachydactyly in this family, we performed a metacarpophalangeal pattern profile (MCPP) for the three patients, which did demonstrate not only brachymesophalangy and brachymatacarpia but brachytelephalaby, which recapitulated what Sentchordi-Montané et al reported and resembled those seen in ACFD (Figure S1). 6 In agreement with the previous report by Sentchordi-Montané et al, 5 we found that IHH heterozygous variants caused broader clinical and radiological manifestations than previously thought. The clinical manifestations of IHH heterozygous variants are variable even within the same family.…”
supporting
confidence: 93%
“…4 Recently, Sentchordi-Montané et al reported the broad spectrum of the clinical and radiological features in families with heterozygous IHH variants. 5 In addition to brachymesophalangy and short stature, affected individuals may have upper limb shortening, distal phalangeal shortening (brachytelephalangy), and metacarpal shortening (brachymetacarpia), associated with cone-shaped epiphyses. 5 Here, we describe a Japanese family with a novel heterozygous mutation in IHH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Skeletal chondrodysplasias caused by Ihh gene inactivation mutations have been reported to be among the most common forms of idiopathic short stature and are clinically characterized by variable degrees of short stature, short limbs, brachydactyly, and narrow thorax with pectus deformities. 2 , 3 , 4 , 5 Currently, there is no effective treatment for these diseases. Although human growth hormone has been used to treat these diseases, little evidence has confirmed the effectiveness of such treatments 4 , 6 due to the lack of an ideal animal model for testing the efficacy of therapeutic strategies and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the patients were born small for gestational age (SGA). Recently, heterozygous pathogenic IHH variants were identified in another cohort with short stature and/or brachydactyly, including the first patient with a complete deletion of IHH , who presented with both short stature and brachydactyly ( 57 ).…”
Section: Defects In Fibronectin-1 Cause Smd-corner Fracture Typementioning
confidence: 99%